Quasi-harmonic RF oscillations in a gyrotropic nonlinear transmission line - Karelin, S.Y.; Krasovitsky, V.B.; Magda, I.I.; Mukhin, V.S.; Sinitsin, V.G. (Вопросы атомной науки и техники, 2018)
The paper considers formation of quasi-monochromatic radio frequency oscillations under the influence of a
short carrier-free pulse of electric current, in the transmission line of doubly connected cross-section partially filled
with a magnetized ferrite. The frequencies and amplitudes of the oscillations are determined by dispersive and nonlinear properties of the structure which are, in their turn, governed by the geometry and size of the line proper, and
the spatial structure of the ferromagnetic material with its intrinsic dispersion. The dependences shown by the
oscillation parameters in physical experiments are reproduced and analyzed via numerical simulation within models
which account separately for different physical properties of the material and the structure. Розглянуто формування радіочастотних квазімонохроматичних осциляцій під впливом короткого
електричного імпульсу без несучої частоти в топологічно двозв’язних лініях передачі, що заповнені
намагніченим феритом. Частота й амплітуда осциляцій, що збуджуються, визначені дисперсійними та
нелінійними характеристиками лінії, що залежать від її розмірів та геометрії, а також власних
дисперсійних властивостей фериту та шаруватої структури заповнення лінії. Залежності параметрів
осциляцій від характеристик системи, що були встановлені в низці експериментів, відтворено в числових
моделях, котрі враховують вказані характеристики окремо. Рассматривается формирование радиочастотных квазимонохроматических осцилляций в
топологически двусвязных передающих линиях, заполненных намагниченным ферритом, под воздействием короткого электрического импульса без несущей частоты. Частота и амплитуда возбуждаемых
осцилляций определяются дисперсионными и нелинейными характеристиками линии, которые зависят
от размеров и геометрии самой линии, а также собственных дисперсионных свойств феррита и слоистой
структуры заполнения. Зависимости параметров осцилляций от характеристик системы, установленные в
ряде экспериментов, воспроизведены в численных моделях, которые раздельно учитывают указанные
характеристики.